The Effects of the Treatment of the Periodic Boundary Condition in TRIAINA Codes with a Pressure Tube Creep Problem - E. H. Ryu; S. Y. Yoo; B. Y. Chung; J. Y. Jung (Science and Technology of Nuclear Installations)
To verify the periodic boundary condition (PBC) treatment which was implemented in a TRI-angle elements induced numerical analyzer (TRIAINA), the pressure tube creep problem is chosen and examined with three cases of normal, 2.5% creep, and 5.0% creep on the aspects of the multiplication factor and relative pin power. The McCARD code is used for the homogenized group constants generation. It is shown that the differences are nearly negligible for the pressure tube creep problem.